Rama ii ebook - Clarke, Arthur C. (Rama, 2012)
In the sequel to the multi-award winning sci-fi novel Rama , a second Raman spaceship enters our solar system and “offers one surprise after another” ( The New York Times ).   Years ago, the enormous, enigmatic alien spacecraft Rama sailed through our solar system as mind-boggling proof that life existed—or  had  existed—elsewhere in the universe. Now, at the dawn of the twenty-third century, another ship is discovered hurtling toward us.   A crew of Earth’s best and brightest minds is assembled to rendezvous with the massive vessel. They are armed with everything we know about Raman technology and culture. But nothing can prepare them for what they are about to encounter on board  Rama II : cosmic secrets that are startling, sensational—and perhaps even deadly.   “A masterpiece . . . one of the year’s best hard SF epics.” — The Houston Post